(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2018)
The research aims to identify the extent of witch the exporting food industry companies in Syria practice their promotional activities (advertising, personal selling, sales promotion, public relations) at the entrance to target international markets. Adopted Find the descriptive approach, style social survey, and be the research community from exporting food industry companies in Syria, and the research sample encompassing (16) did not stop the export despite the current situation, where the distribution of the questionnaire research on the export and marketing officer tool in this companies, the number of distributed questionnaires was reached (150) form, where the re-ones (137) complete and valid form for statistical analysis, and by the answer was (91.33%). The results showed that the exporting companies in the study practiced my advertising, personal selling moderately, while the exercise of my public relations and sales promotion weakly. واقع النشاط الترويجي للشركات الصناعية في الأسواق الدولية دراسة ميدانية على شركات صناعات الأغذية المصدرة في سورية هدف البحث إلى التعرف على مدى ممارسة شركات صناعة الأغذية المصدرة في سورية للأنشطة الترويجية (الإعلان, البيع الشخصي, ترويج المبيعات, العلاقات العامة) عند الدخول إلى الأسواق الدولية المستهدفة. اعتمد البحث على المنهج الوصفي, وأسلوب المسح الاجتماعي, وتكون مجتمع البحث من شركات الصناعات الغذائية المصدرة في سورية, أما عينة البحث فشملت (16) شركة لم تتوقف عن التصدير بالرغم من الأوضاع الحالية, حيث تمّ توزيع الاستبانة (أداة البحث) على مسؤولي التصدير والتسويق في هذه الشركات, وقد بلغ عدد الاستمارات الموزعة (150) استمارة, حيث أعيد منها (137) استمارة كاملة وصالحة للتحليل الإحصائي, وبنسبة إجابة بلغت (91.33%). أظهرت النتائج أنّ الشركات المصدرة محل الدراسة تمارس نشاطي الإعلان والبيع الشخصي بدرجة متوسطة, بينما كانت ممارستها لنشاطي العلاقات العامة وتنشيط المبيعات بدرجة ضعيفة.